How Well Does the Nipissing District Developmental Screen (NDDS) Identify Communication Problems in Infants?. (1st June 2016) - Heuvel, M Van den; Borkhoff, C; Koroshegyi, C; Zabih, W; Maguire, J; Birken, C; Parkin, P
Abstract: BACKGROUND: Communication problems are often the first presenting problem in infants with developmental disabilities. With early detection, intervention can start. The 18-month Nipissing District Developmental Screen (NDDS) was created as a developmental checklist for use in primary care. The Infant Toddler Checklist (ITC) is a validated questionnaire for detecting communication problems. Our objective was to examine how well the 18-month NDDS identifies communication problems. We therefore assessed the convergent validity of the 18-month NDDS with the ITC as a gold standard. OBJECTIVES: To examine how well the 18-month NDDS identifies communication problems. To compare parents' answers to a similar question, "How many different words does your child use?", on both checklists. DESIGN/METHODS: Healthy children (n = 348, 55% male, mean age 18.6 months, SD 0.7) were recruited during scheduled health supervision visits. Parents completed both the 18-months NDDS and ITC. We assessed the convergent validity of the 18-month NDDS with the ITC as a gold standard. Correlation (Spearman) and the level of agreement (Cohen's kappa, sensitivity, specificity) were calculated. For our secondary outcome, we compared the percentage of agreement between the answers to the same question on both instruments. RESULTS: On the NDDS, 138 (39.7%) children had "one or more flags" (+1 NDDS) and 54 (15.8%) children had "two or more flags" (+2 NDDS). 13 (3.7%) infants had a concern on the total ITC score, 31 (8.9%) a speech-, 9 (2.6%) a social -, and 14 (4.0%) a symbolic concern.The +2 NDDS had a medium correlation (Spearman's rho 0.42) and a fair agreement (Cohen's kappa 0.32) with the ITC. Sensitivity and specificity of the NDDS using the +1 and + 2 flag cut-offs in detecting concerns compared with the ITC are shown in the table.The similar question about number of words spoken by 18-month old infants revealed agreement between the NDDS and ITC; 24.4% versus 30.8% of the 18-month old infants did not speak 20 words or more respectively. CONCLUSION: Infants with a severe overall communication delay were identified with the 18-months NDDS. The low sensitivity of the 2+ NDDS flag in detecting speech and social concerns suggests that infants who could benefit from early interventions may not be identified.The low specificity of the 1+ NDDS flag may cause unnecessary concerns for parents.For the early identification of all levels of communicationdelays, we recommend using a standardized questionnaire like the ITC.